Avaliação do uso de uma interface homem-computador baseada em eletromiografia em indivíduos com e sem alterações neuro-motoras de membros superiores - Prado, Reuder Pereira (2013)
Recently our research group has developed a human-computer interface called Muscle Academy, based on the electrical activity detected from the surface of muscles ( electromyography - EMG ) . In this study, 40 subjects were evaluated: 30 patients without disorders in the upper limbs and 10 individuals with disorders in the upper limbs, to evaluate the use of the Muscle Academy in different situations. The 30 individuals without disorders in the upper limbs were divided into 3 groups of 10 people face , who performed the experimental protocol using different distances between the buttons to be clicked ( IMs distance of 4 cm, with a distance of GII and GIII 7.5 cm with a distance of 15 cm ) and group individuals with upper limb disorders conducted the survey with 15 cm distance between the buttons to be clicked. The results showed a significant statistical difference between time (ms) average spending of a button to go to the next and clicking the experimental groups, especially when compared with those without disorders in the upper limbs and upper limb disorders, both with the same distance between buttons, however, the development of learning of all subjects factors was similar, reducing the average time taken to complete the tasks in the course of the sessions. We conclude that the tool is a good resource for monitoring progress of individuals with and without upper limb disorders and learning factors; the distance between them and the buttons size influenced the average time (ms) spent to go from one button to another and clicking while the meaning which individuals have followed (clockwise , counterclockwise and random) did not exert a statistically significant influence.